STUDENT VOICES ON KAHOOT: AN EXPLORATION OF EFL LEARNERS' MOTIVATION IN HIGH SCHOOL - Prihatini Nur Rachma; Ma'mun, Nadiah; Karnadi Hasan (University of Muhammadiyah Malang, 2024)
Science and technology development has touched all aspects of life, and education is no exception. The effect of technological development is used to improve the service and quality of education which is always demanded to adapt to the changing times. The implementation of digital technology in the learning process is by using the appropriate learning media, so it can improve the quality of learning outcomes and provide motivation to students. The use of digital technology in the learning process is known as game-based learning. With this method, students are expected to explore learning materials with the help of technology, so that students get a new learning experience that is unique and fun and can increase their learning motivation in learning English. One of these digital platforms is Kahoot. This study aims to determine students' perceptions of the use of Kahoot media to enhance motivation in learning English in Class XII. Data analysis was conducted by descriptive quantitative based on the results of a questionnaire survey that included questions about the use of Kahoot in enhancing students' learning motivation in English learning. The results showed that 18 students of class XII had a fairly positive perception of the use of Kahoot in enhancing motivation in English learning. Based on these results, it can be concluded that Kahoot can enhance students' learning motivation in English learning and it is necessary to increase the intensity of its use to ensure that students get a joyful learning experience and enhance their motivation.